Nonlinear wave forces on large-scale submerged tunnel element. (January 2016) - Wu, Z.W.; Liu, J.K.; Liu, Z.Q.; Lu, Z.R.
Abstract: This paper presents parametric studies of nonlinear wave forces on large-scale submerged tunnel element. A transportation project of submerged tunnel element under irregular wave conditions is taken as the research background. Three-dimensional diffraction potential and radiation potential associating with the motion of the floating body are utilized, and an efficient three dimensional Green function is implemented to solve the radiation-diffraction problem. A computational method for calculating the nonlinear wave forces of the submerged tunnel element is developed. The present method is validated by the existed methods and experimental data, and good agreements are observed for all test models. The effects of wave parameters and structural parameters on the second-order nonlinear wave forces are studied. Results from the present study can provide valuable recommendations for the weather window and downtime frequencies, the configuration of tugboats, the arrangement of sea-route, and the size and type of the design and construction of the submerged tunnel element. Highlights: Nonlinear wave forces on long and large-scale immersed tunnel element are studied. A transportation project of immersed tunnel element is taken as the research background. A computing method of calculating the nonlinear wave forces is developed. Parameter studies of second-order nonlinear wave forces are studied. Valuable recommendations can be obtained from the present study.